2019
DOI: 10.21315/eimj2019.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perception of the Educational Environment among Health Sciences Students at The University of Rwanda: A Mixed Methods Study

Abstract: The educational environment (EE) plays a very important role in effective learning. However, information about the quality of the EE at the University of Rwanda (UR) is limited. We aimed to explore the perception of health sciences students about their EE at UR. We used a mixed methods design. Of 606 health sciences students in total, 241 participants were recruited for a quantitative survey using the Dundee Ready Education Environment Measure (DREEM) questionnaire. Additionally, we purposively recruited 10 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results showed that behavioural intentions were positively related to LLINs use, IRS acceptance, and draining stagnant water in case present. However, no evidence supported the hypotheses that either availability or accessibility of LLINs moderated the relationship between behavioural intentions and actual use of LLINs (Table 3. 4). Looking at the control variables, slight significant associations between gender, education and use of LLINs, and a significant positive relationship between age and draining stagnant water were observed.…”
Section: Moderation Analysis Of Behavioural Intentions and Use Of Malmentioning
confidence: 88%
“…The results showed that behavioural intentions were positively related to LLINs use, IRS acceptance, and draining stagnant water in case present. However, no evidence supported the hypotheses that either availability or accessibility of LLINs moderated the relationship between behavioural intentions and actual use of LLINs (Table 3. 4). Looking at the control variables, slight significant associations between gender, education and use of LLINs, and a significant positive relationship between age and draining stagnant water were observed.…”
Section: Moderation Analysis Of Behavioural Intentions and Use Of Malmentioning
confidence: 88%